2023
DOI: 10.1136/bmjresp-2023-001617
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the risk of transmission of respiratory viral infections in childcare centres: protocol for the DISeases TrANsmission in ChildcarE (DISTANCE) multicentre cohort study

Abstract: IntroductionChildcare centre is considered a high-risk setting for transmission of respiratory viruses. Further evidence is needed to understand the risk of transmission in childcare centres. To this end, we established the DISeases TrANsmission in ChildcarE (DISTANCE) study to understand the interaction among contact patterns, detection of respiratory viruses from environment samples and transmission of viral infections in childcare centres.Methods and analysisThe DISTANCE study is a prospective cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Epidemiological studies have consistently shown a link between vitamin D deficiency and increased susceptibility to infectious diseases, including respiratory infections [ 6 , 7 , 8 ]. This association is of particular interest in preschool children who are at a higher risk of developing respiratory infections due to their still-developing immune systems and high exposure rates in communal settings, such as daycare and preschool [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have consistently shown a link between vitamin D deficiency and increased susceptibility to infectious diseases, including respiratory infections [ 6 , 7 , 8 ]. This association is of particular interest in preschool children who are at a higher risk of developing respiratory infections due to their still-developing immune systems and high exposure rates in communal settings, such as daycare and preschool [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%